Reassessing the contributions of Black inventors to the golden age of innovation - Michael Jeffrey Andrews; Jonathan Rothwell (Essays in Economic & Business History (EEBH), 2023)
During the Second Industrial Revolution and subsequently, it is widely believed that Black Americans contributed disproportionately little to the economic development of the United States, especially in comparison to European Americans and immigrants from Europe. Yet, Black Americans tended to live in entirely different institutional environments than other Americans, particularly in the South under Jim Crow laws. Using a new database that matches inventors to census records, we find that patenting rates for Black Americans living in the North were very similar to patenting rates for White Americans from 1870 to 1940; in some decades and states, Northern Black patenting rates exceeded the patenting rate for White Americans. In the South, patenting rates were low for both Black and White Americans, while patenting rates for Northern Black residents were far higher than those for Southern White residents. We additionally find that Black Americans from all regions were responsible for more patents than immigrants from all but two countries (Germany and England). In total, we estimate that African Americans invented more than 50,000 patents over the period. Thus, when freed of extreme political oppression, Black Americans demonstrated a level of inventiveness that matched the most inventive groups in US history.
Keywords: N0; N8; N3; O3; O34; J15; 330; Patents; Innovation; Race; Economic Geography